2020
DOI: 10.1002/pbc.28603
|View full text |Cite
|
Sign up to set email alerts
|

New dosing nomogram and population pharmacokinetic model for young and very young children receiving busulfan for hematopoietic stem cell transplantation conditioning

Abstract: Background Busulfan (Bu) is the cornerstone of conditioning regimens prior to hematopoietic stem cell transplantation, widely used in both adults and children for the treatment of malignant and nonmalignant diseases. Despite an intravenous formulation, interindividual variability (IIV) remains high and optimal exposure difficult to achieve, especially in neonates and infants. Procedure To ensure both efficacy and safety, we set up in 2005 an observational study designed for children not fully assessed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Bu, taking into consideration the genetic marker for GSTA1 metabolic capacity. Previous large multicentric PopPK studies were performed in mixed pediatric populations 16,17,21,33 . The McCune et al 16 model also included adult patients and can therefore be applied in a wider population.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bu, taking into consideration the genetic marker for GSTA1 metabolic capacity. Previous large multicentric PopPK studies were performed in mixed pediatric populations 16,17,21,33 . The McCune et al 16 model also included adult patients and can therefore be applied in a wider population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous large multicentric PopPK studies were performed in mixed pediatric populations. 16 , 17 , 21 , 33 The McCune et al 16 model also included adult patients and can therefore be applied in a wider population. However, these studies did not account for markers for GSTA1 metabolic capacity, which were reported in several studies to significantly influence Bu PK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations